Flood tolerant variety IR13F265 (NSIC Rc 590) for the Philippines - CGIAR Research Program on Rice (2020)
The variety was recommended for release in 2020. It now needs to be taken forward and multiplied to produce quality seeds and provided to farmers with an adequate agronomic package for cultivation.